The Routledge Handbook of European Integrations - Hoerber, Thomas; Weber, Gabriel; Cabras, Ignazio (Taylor & Francis, 2022)
CAP; Common Market; EDA; Erasmus; European integration; European Armament; CERN; European media; Eurozone; ITER; European tourism